Role of serum carbohydrate antigen 19-9 and carcinoembryonic antigen in distinguishing between benign and invasive intraductal papillary mucinous neoplasm of the pancreas - Fritz, Stefan; Hackert, Thilo; Hinz, Ulf; Hartwig, Werner; Büchler, Markus W.; Werner, Jens (The British journal of surgery, 2011)
Intraductal papillary mucinous neoplasm (IPMN) of the pancreas has malignant potential. Although serum levels of carbohydrate antigen (CA) 19-9 and carcinoembryonic antigen (CEA) are known to be raised in pancreatic ductal adenocarcinoma, little has been reported about their significance in IPMN.Preoperative CA19-9 and CEA levels were measured in consecutive patients undergoing surgical resection for IPMN. Results were correlated with histopathological and clinical features.In 142 patients, raised CEA and CA19-9 serum levels were significantly associated with invasiveness in both branch-duct and main-duct/mixed-type IPMN. Some 74 per cent of patients with an invasive IPMN had raised levels of CA19-9, compared with only 14 per cent who had non-invasive tumours. With a cut-off level of 37 units/ml, CA19-9 had a specificity of 85·9 per cent, a negative predictive value of 85·9 per cent, a positive predictive value of 74·0 per cent and accuracy of 81·7 per cent. Overall, 80 per cent of patients with an invasive IPMN had raised serum levels of CA19-9 and/or CEA compared with only 18 per cent of those with a non-invasive tumour (P < 0·001).Serum CA19-9 is a useful non-invasive preoperative tool for differentiating between invasive and benign IPMN, and should be taken into account in the decision to offer surgery. Patients with an IPMN and positive tumour markers have a high risk of malignant disease.
Online veröffentlicht 14. Oktober 2010
Gesehen am 27.04.2023